Irisin attenuates SARS-CoV-2 entry into cells and cell damage in 2D and 3D cultures of human subcutaneous adipocytes - De Sibio, Maria Teresa [UNESP]; Vieira, Ester Mariane [UNESP]; Da Rocha, Paula Barreto [UNESP]; De Oliveira, Miriane [UNESP]; Olímpio, Regiane Marques Castro [UNESP]; Peghinelli, Vinícius Vigliazzi [UNESP]; Mathias, Lucas Solla [UNESP]; Tilli, Helena Paim [UNESP]; Gonçalves, Bianca Mariani [UNESP]; Deprá, Igor [UNESP]; Bravin, Maria Beatriz [UNESP]; Lourenço, Mariana Menezes [UNESP]; et al. (Bioscientifica, 2025)
Introduction: COVID-19 is associated with an inflammatory pathophysiology and, when associated with chronic diseases, can trigger severe infection and increase death risk. Irisin, a hormone produced by skeletal muscle during physical activity, has demonstrated therapeutic effects against metabolic disorders and exhibits anti-inflammatory and antioxidant effects. There is great interest in investigating irisin's influence on the interaction between SARS-CoV-2 and host cells. The aim of the present study is to investigate the role of irisin in viral infection in monolayers (2D) or three-dimensional (3D) cell cultures of human subcutaneous adipocytes infected with a SARS-CoV-2 pseudovirus (PV). Materials and methods: Preadipocytes were cultured to maturity in 2D or 3D conditions and divided into four groups: Group 1: adipocytes with no treatment; Group 2: adipocytes optimized for angiotensin-converting enzyme 2 (ACE2) expression; Group 3: adipocytes optimized for ACE2 expression, and then exposed to SARS-CoV-2 pseudovirus (ACE2+PV); and Group 4: adipocytes treated with irisin 20 nM for 24 h, optimized for ACE2 expression and exposed to PV (ACE2+I+PV). Fluorescence levels of SARS-CoV-2 PV and ACE2 were measured to investigate cell infection; lactate dehydrogenase (LDH) activity to investigate cytotoxicity; and malondialdehyde (MDA) and protein carbonylation to assess oxidative stress levels. Results and discussion: Irisin significantly reduced viral particle (PV) capture in 2D and 3D conditions. In addition, irisin decreased LDH release, MDA, and protein carbonylation levels, both in 2D and 3D conditions. Conclusion: The results indicate irisin as a promising therapeutic target against COVID-19 pathophysiology by reducing viral entry into adipose cells as well as reducing cytotoxicity and oxidative stress indicators.